Cholera Outbreak in Khon Kaen, Thailand, 2007: Warning of Multi-drug ResistanceVibrio cholerae - Sangsawang, Choopong; Tanalad, Wilai; Chatpituk, Pongthon; Khadthasrima, Naretrit; Tungsawut, Sasitorn; Juntee, Somkid; Ruamtawee, Chumpon; Changtong, Wattjana; Jiraphongsa, Chuleeporn (Journal of Health Science of Thailand, 2018)
In mid September 2007, Khon Kaen province, Thailand was affected by V. cholerae El TorOgawa resisting to multi-drugs. Bureau of Epidemiology conducted joint investigation with thelocal officers in order to describe the characteristics of the outbreak, including microbial resistance,and to provide recommendations for control. A descriptive study was conducted; a case was definedas any people in Khon Kaen who had diarrhea and positive for V. cholerae by rectal swab cultureduring 15 September - 17 October 2007. Drugs sensitivity reports of the 2007 outbreak in KhonKaen was compared with the 1998-2000 outbreaks in the same region. Totally 218 reported casesfrom 9 of 25 districts (AR 12.5/100,000 population) with one death (CFR 0.4%). Of 155 isolatedstrains of V. cholerae El Tor Ogawa were tested for drug sensitivity by standard diffusion technique,97-100 percent resisted to tetracycline and cotrimoxazole, 98 percent intermediately resisted toerythromycin and 100 percent were sensitive to norfloxacin. However, the mean of inhibition zoneof norfloxacin comparing 1998-2000 and 2007 were significantly decreasing from 29.3 mm to 22.5mm (mean difference 6.8 mm, 95%CI 6.2, 7.4). Accordingly awareness of quinolone resistancemust be a cause for concern. Proper antibiotic used must follow the standardized guideline. Drugcompliance will be completely observed. Information on cholera microbial resistance under labora-tory surveillance should be shared and distributed to any responsible organizations including physi-cians.